2022
DOI: 10.1039/d1cp04885f
|View full text |Cite
|
Sign up to set email alerts
|

CASPT2 molecular geometries of Fe(ii) spin-crossover complexes

Abstract: Using fully internally contracted (FIC)-CASPT2 analytical gradients, geometry optimizations of spin-crossover complexes are reported. This approach is tested on a series of Fe(II) complexes with different sizes, ranging from 13...

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 82 publications
1
12
0
Order By: Relevance
“…C 2 symmetry is imposed in the case of [Fe(bpy) 3 ] 2+ and no symmetry restrictions are applied in [Fe(mtz) 6 ] 2+ . The Fe–N distances for the LS and HS states in the relaxed scan minima are in good agreement with the (XMS-)CASPT2 fully optimized geometries by Finney et al 21 Further information about the relaxed scan can be found in the ESI †…”
Section: Thermal Relaxationsupporting
confidence: 84%
“…C 2 symmetry is imposed in the case of [Fe(bpy) 3 ] 2+ and no symmetry restrictions are applied in [Fe(mtz) 6 ] 2+ . The Fe–N distances for the LS and HS states in the relaxed scan minima are in good agreement with the (XMS-)CASPT2 fully optimized geometries by Finney et al 21 Further information about the relaxed scan can be found in the ESI †…”
Section: Thermal Relaxationsupporting
confidence: 84%
“…Although CASPT2 (and NEVPT2) analytical gradients have been available for several years, [135–140] most studies currently employed structures obtained at the DFT level of theory or from crystallographic data. We are aware of only one systematic study on the performance of CASPT2 in the description of TM complex geometries [141] …”
Section: Methodsmentioning
confidence: 99%
“…We are aware of only one systematic study on the performance of CASPT2 in the description of TM complex geometries. [141]…”
Section: Multireference Configuration Interaction and Second-order Mu...mentioning
confidence: 99%
“…Virtual high-throughput screening (VHTS) and machine learning (ML)-accelerated chemical discovery with approximate density functional theory (DFT) have started to address the combinatorial challenges in discovering and designing functional molecules and materials. Despite the balanced trade-off in computational cost and accuracy, DFT can fail prominently for promising materials, such as the chemical space of transition metal complexes (TMCs). TMCs may have strong multireference (MR) character due to near-degenerate orbitals, , which cannot be accurately described in DFT due to the single-reference (SR) nature of the noninteracting wave function .…”
Section: Introductionmentioning
confidence: 99%